Antifungal Efficacy of Ganoderma lucidum and Clotrimazole for Treatment of Denture Stomatitis: A Randomized Clinical Trial - Fahimeh Pakravan; Afsaneh Yegdaneh; Somayeh Taymouri; Shiva Rahimi; Negin Ghahremani (Frontiers in Dentistry)
Objectives: This study aimed to compare the antifungal efficacy of Ganoderma lucidum (G. lucidum) and clotrimazole for treatment of denture stomatitis (DS).